(3GdebQHs - (3GHf YUahQ , Ydj Hf eDef Hf eMeO GdMVQej GdGTHjdj, CHh GdMSf,J (B669 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3hHYO, aEfg deG cGf Yde GdYQHjI ef CLd GdYdhe bOQkG hcGfJ CcKQ GdehVhYGJ ajg dG JHQO ZdjdkG s
(3BNQgG (B:s
(3hjLhR GdbjGS Ydi cKQ GSJYeGdg ef Pdc heG de jcKQ adG SHjd ddbjGS Ydjg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3aj GdeYgO fSNI CNQi GfXQ GdLRA GdChd ef (B166-170 (3fMhs
(3egedI GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs